The DNMT1‐associated lncRNA UCA1 was upregulated in TK6 cells transformed by long‐term exposure to hydroquinone and benzene‐exposed workers via DNA hypomethylation. Issue 12 (6th October 2021) - Pan, Zhijie; Zhong, Bohuan; Ling, Xiaoxuan; Zhang, Haiqiao; Tan, Qiang; Huang, Dongsheng; Chen, Jialong; Zhang, He; Zheng, Dongyan; Li, Huifang; Chen, Xiaobing; Liu, Linhua
Abstract: Exposure to benzene or its metabolite hydroquinone (HQ) is a risk factor for a series of myeloid malignancies, and long noncoding RNAs play an important role in the process of pathogenesis. Urothelial cancer‐associated 1 (UCA1) functions as an oncogene in the development of acute myeloid leukemia. However, the association between DNMT1 and UCA1 with benzene or HQ exposure has not been explored. We characterized UCA1 expression in cells briefly exposed to HQ (HQ‐ST cells) and HQ‐induced malignantly transformed (TK6‐HT cells) treated with 5‐aza‐2ʹ‐deoxycytidine (5‐AzaC) or trichostatin A (TSA). Compared to that in control cells, UCA1 expression was increased, whereas DNMT1 was decreased in HQ‐ST cells and TK6‐HT cells treated with 5‐AzaC or TSA. Moreover, UCA1 expression was also upregulated and positively correlated with benzene exposure time in benzene‐exposed workers. Furthermore, the expression of UCA1 was negatively associated with the DNA methylation level of its promoter in benzene‐exposed workers. DNMT1 rather than DNMT3b knockout in TK6‐HT cells activated the expression of UCA1 by inducing its promoter hypomethylation. These results suggest that benzene or HQ exposure leads to UCA1 upregulation via DNA hypomethylation in the UCA1 promoter, which is mediated by DNMT1.